Examining pulmonary embolism - Raboin, Dana; HSTN (Texas : Primedia Healthcare, 2002)
(Producer) Approximately 200,000 hospitalized patients will experience a pulmonary embolism (PE) this year. Twenty-five percent of these patients will die, with two-thirds of these deaths occurring within 30 minutes of emboli lodging in the pulmonary artery. Pulmonary embolisms remain difficult to diagnose and treat. This presentation focuses on prevention, common causes and treatments when caring for a patient with a pulmonary embolism. Pharmacological management is also emphasized
Dana Raboin
Keywords: Pulmonary Embolism -- diagnosis -- Nurses' Instruction; Pulmonary Embolism -- therapy -- Nurses' Instruction; Venous Thrombosis -- complications -- Nurses' Instruction